Riemann operator function. Cayley’s transformation - Makarov, V. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 510 We study a new class of special functions called Laguerre–Bessel polynomials (PLBs), which play the same role as Laguerre polynomials in the case of application of the Cayley transformation to the evaluation of the operator exponent. The generating function for PLBs is a Bessel operator function of the first kind of zero order obtained by replacing its operator argument by its Cayley transformation. It is shown that the PLBs coincide with a new class of 2-orthogonal polynomials with an accuracy of up to a linear transformation. It is shown that the PLBs are classical in the Hahn–Maroni sense because their normalized derivatives also form a class of 2-orthogonal polynomials with an accuracy of up to a linear transformation. We determine the following characteristics traditional for the polynomial classes: explicit representation, recurrence relations, and the differential equations of the minimal third order.